Implementing a genre-based approach to teaching writing in secondary schools: an empirical study of vocational school students (Conference on English Language Teaching, 2023)
This study utilized a classroom action research design to examine the efficacy of agenre-based approach in improving the writing skills of vocational school students.Thirty-four secondary school students in a Kutai Kartanegara East Kalimantan vocationalschool were instructed to use a genre-based approach for twelve weeks in thisinvestigation. The strategy included teaching students exploratory and exploratory writingand providing feedback and opportunities for revision. Data collected through classroomobservations, student work samples, and interviews supported the findings. The researchdiscovered that genre-based instruction improved students' writing abilities. The student'sabilities to write exploratory and procedural texts, employ appropriate language featuresand structures, and organize their thoughts were enhanced. In addition, the student'swriting motivation and engagement increased. This study suggests a genre-basedinstructional strategy can improve students' writing abilities. Students can develop theirwriting skills systemically and systematically, preparing them for various writing duties andassessments. The study has significant implications for secondary school instructors andcurriculum designers who wish to improve students' writing abilities. Additionally, ithighlights the significance of classroom action research.